Discrimination between wild type and heterozygous piebald ball python (Python regius) by PCR and qPCR - R. Kumsiri; N. N. Yin; P. Kanchanaphum (Brazilian Journal of Biology)
Abstract The ball python, also known as Python regius, is a popular exotic pet due to its beautiful colors and patterns, particularly the piebald variety. However, it can be challenging to distinguish between the wild type and heterozygous piebald (het piebald) phenotypes. This study employs PCR and qPCR techniques to differentiate between these two genotypes. The PCR product size for both the wild type and het piebald was 255 bp. However, the intensity of the PCR product from the wild type was twice that of the het piebald, and no PCR product was detected in the piebald individuals. Additionally, the Ct value for the wild type was lower than that of the het piebald. The qPCR analysis revealed a 15.45% difference between the two groups. Therefore, PCR and qPCR effectively distinguish between the wild type and het piebald genotypes of ball pythons.